2012
DOI: 10.1371/journal.pone.0029989
|View full text |Cite
|
Sign up to set email alerts
|

Mda-9/Syntenin Is Expressed in Uveal Melanoma and Correlates with Metastatic Progression

Abstract: Uveal melanoma is an aggressive cancer that metastasizes to the liver in about half of the patients, with a high lethality rate. Identification of patients at high risk of metastases may provide indication for a frequent follow-up for early detection of metastases and treatment. The analysis of the gene expression profiles of primary human uveal melanomas showed high expression of SDCBP gene (encoding for syndecan-binding protein-1 or mda-9/syntenin), which appeared higher in patients with recurrence, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 39 publications
(58 reference statements)
2
69
0
Order By: Relevance
“…Syntenin is also known as mda-9 and was originally cloned from human melanoma cells. As a PDZ domain-containing molecule, syntenin can exert multiple roles and regulate diverse and central physiologic processes (8,9). The function of syntenin in cancer has attracted increasing attention for its important roles in the development of various cancers, including melanoma, breast and bladder cancer (10,12,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Syntenin is also known as mda-9 and was originally cloned from human melanoma cells. As a PDZ domain-containing molecule, syntenin can exert multiple roles and regulate diverse and central physiologic processes (8,9). The function of syntenin in cancer has attracted increasing attention for its important roles in the development of various cancers, including melanoma, breast and bladder cancer (10,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The function of syntenin in cancer has attracted increasing attention for its important roles in the development of various cancers, including melanoma, breast and bladder cancer (10,12,13). It has been confirmed that syntenin is highly expressed in several cancer cells and tissues, and it is involved in the progression of cancer, including cancer cell growth, invasion and metastasis (9,21,22). However, its function in the development of hepatoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients in the two datasets were composed of 63 and 29 samples, respectively [17,18]. All the samples were performed on Affymetrix Human Genome U133 Plus 2.0 Array.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic tumors formed within 4-6 weeks after injection [71]. This method facilitates tumor cells to colonize the liver through the portal circulation system, is applicable for many tumors, and readily lends itself to the evaluation of immunotherapeutic and chemotherapeutic approaches for the treatment of liver metastases; it has also been used to study the mechanisms that lead to hepatic metastases from primary uveal melanoma [67,72,73]. …”
Section: Animal Models Of Metastatic Uveal Melanomamentioning
confidence: 99%